On a class of systems of equations of the Lax type - Lunyov, A. A.; Oliynyk, E. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The non-linear system of equations of the Lax type is investigated. It is a basis of the triangular models for commutative systems of linear non-self-adjoint operators. In some cases, the complete description of solutions of this system is found.